Increased lipid peroxidation in trained men after 2 weeks of antioxidant supplementation - Lamprecht, M.; Hofmann, P.; Greilberger, J. F.; Schwaberger, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
Purpose: To assess the effects of an encapsulated antioxidant concentrate (EAC) and exercise on lipid peroxidation (LIPOX) and the plasma antioxidant enzyme glutathione peroxidase (Pl-GPx). Methods: Eight trained male cyclists (VO2max > 55 ml · kg-1· min-1) participated in this randomized, placebo-controlled, double-blinded, crossover study and undertook 4 cycle-ergometer bouts: 2 moderate exercise bouts over 90 min at 45% of individual VO2max and 2 strenuous exercise bouts at 75% of individual VO2max for 30 min. The first 2 exercise tests—1 moderate and 1 strenuous—were conducted after 4 weeks wash-out and after 12 and 14 days of EAC (107 IU vitamin E, 450 mg vitamin C, 36 mg b-carotene, 100 µg selenium) or placebo treatment. After another 4 weeks wash-out, participants were given the opposite capsule treatment and repeated the 2 exercise tests. Physical exercise training was equal across the whole study period, and nutrition was standardized by a menu plan the week before the tests. Blood was collected before exercise, immediately postexercise, and 30 min and 60 min after each test. Plasma samples were analyzed for LIPOX marker malondialdehyde (MDA) and the antioxidant enzyme pl-GPx. Results: MDA concentrations were significantly increased after EAC supplementation at rest before exercise and after moderate exercise (p < .05). MDA concentrations showed no differences between treatments after strenuous exercise (p > .1). Pl-GPx concentrations decreased at all time points of measurement after EAC treatment (p < .05). Conclusions: The EAC induced an increase of LIPOX as indicated by MDA and decreased pl-GPx concentrations pre- and postexercise.